PROBLEMS OF STUDENTS’ PHYSICAL AND MATHEMATICAL TRAINING IN CONDITIONS OF LEVEL EDUCATIONAL SYSTEM OF POLYTECHNIC UNIVERSITY - Aleksey I. Tsaplin (Высшее образование в России, 2022)
The article examines the organizational and methodological problems of training at the faculty of applied mathematics and mechanics in Perm National Research Polytechnic University. The author asserts that in conditions of two-level education it is possible to overcome the crisis of physical and mathematical training of university entrants and to graduate competitive specialists in conditions of innovation development of country’s economy.